Acute effect of resistance training on cognitive function of Costa Rican older adults - Hernández Gamboa, Rebeca (2022)
Different types of exercise interventions have shown to improve cognitive performance; however, there is scarce evidence on the acute effect of resistance training (RT) on cognitions in older adults. The purpose of this study is to determine the acute effect of RT on cognitive performance in healthy older adults. 45 adults (Mean age = 65.3 ± 3.7 yr.) were randomly allocated to one of three groups: high-intensity RT (G1), low-intensity RT (G2), or inactive control (G3). Participants completed cognitive tests assessing processing speed, visuospatial processing, executive function, and cognitive control, working memory and immediate memory. The RT protocol for G1 and G2 consisted of six exercises. A 3x2 ANCOVA was performed with education as a covariate. Significant improvements were found on visuospatial processing in G1 (Pre = 61.6 ± 2.1 vs. Post = 69.7 ± 2.4; 95%CI = 4.8, 11.4; p ≤ 0.001) and G2 (Pre = 62.4 ± 2.2 vs. Post = 67.0 ± 2.5; 95%CI = 1.2, 8.1; p = 0.009). Other tested cognitive abilities were unchanged by acute exercise or rest. Acute RT enhanced or maintained cognitive performance in older adults. It was possible to successfully perform 1RM tests with older adults. Additional evidence is needed to determine effective protocols to improve cognition in older adulthood.